Adaptive design: adaptation and adoption of patient safety practices in daily routines, a multi-site study - Connie Dekker - van Doorn; Linda Wauben; Jeroen van Wijngaarden; Johan Lange; Robbert Huijsman (BMC, 2020)
Abstract Background Most interventions to improve patient safety (Patient Safety Practices (PSPs)), are introduced without engaging front-line professionals. Administrative staff, managers and sometimes a few professionals, representing only one or two disciplines, decide what to change and how. Consequently, PSPs are not fully adapted to the professionals' needs or to the local context and as a result, adoption is low. To support adoption, two theoretical concepts, Participatory Design and Experiential Learning were combined in a new model: Adaptive Design. The aim was to explore whether Adaptive Design supports adaptation and adoption of PSPs by engaging all professionals and creating time to (re) design, reflect and learn as a team. The Time Out Procedure (TOP) and Debriefing (plus) for improving patient safety in the operating theatre (OT) was used as PSP. Methods Qualitative exploratory multi-site study using participatory action research as a research design. The implementation process consisted of four phases: 1) start-up: providing information by presentations and team meetings, 2) pilot: testing the prototype with 100 surgical procedures, 3) small scale implementation: with one or two surgical disciplines, 4) implementation hospital-wide: including all surgical disciplines. In iterations, teams (re) designed, tested, evaluated, and if necessary adapted TOPplus. Gradually all professionals were included. Adaptations in content, process and layout of TOPplus were measured following each iteration. Adoption was monitored until final implementation in every hospital's OT. Results 10 Dutch hospitals participated. Adaptations varied per hospital, but all hospitals adapted both procedures. Adaptations concerned the content, process and layout of TOPplus. Both procedures were adopted in all OTs, but user participation and time to include all users varied between hospitals. Ultimately all users were actively involved and TOPplus was implemented in all OTs. Conclusions Engaging all professionals in a structured bottom-up implementation approach with a focus on learning, improves adaptation and adoption of a PSP. As a result, all 10 participating hospitals implemented TOPplus with all surgical disciplines in all OTs. Adaptive Design gives professionals the opportunity to adapt the PSP to their own needs and their specific local context. All hospitals adapted TOPplus, but without compromising the essential features for its effectiveness.